Teaching Civilization in EFL courses for Third Year Classes in Algerian Secondary Schools (مجلة الواحات للبحوث والدراسات, 2025)
This paper aims to examine the status of civilization as a cultural theme in the EFL teaching in the third year program in Algerian secondary schools. It also investigates the way it is taught to learners and its impact on promoting the learning process of cultural knowledge that is essential for language learners.  This examination is based on a document analysis of the third year textbook and a semi-structured interview for ten Algerian secondary school teachers. The main findings elucidate that teaching civilization is integrated in language tasks where language is contextualized through the content of this theme. The topics inserted covered different civilizations and not only that of the target culture and history of English language native speakers. Additionally, the participants revealed that the teaching instructions and content of civilization are in need of update, calling for huge reforms to enhance the teaching program and content.Keywords:Teaching, civilization, EFL, Content, Textbook.